Prácticas de enseñanza de iniciación a la lecto-escritura en Educación Inicial II en la escuela de educación básica El Buen Saber - Quiroga Quisaguano Talía Monserrath (2015)
This case study looks at how they are carrying out teaching practices, considering the lack of studies and analyzes in this educational field which has kept off a real vision of teaching practice about pre reading and pre prewriting at the initial level. In the research we observed and analyzed the methodological process of class time, taking into account variables like: curriculum planning, methodological process, student-teacher interaction, academic tasks and academic evaluation. The study was conducted through the collection of information in person, through a field study using participant observation, also observation files and field diary for lifting data. The investigation resulted in a teaching practice with poor scientific foundations and theoretical knowledge of education themselves, also to not provide spaces for the development of meaningful learning, because it neglects the use of planning and the breach school hours, academic homework are not explained, the methodology of game-work is not taken into account, the assessment is based on the quality and thoroughness of the activities, but not in the capacity of students, the relationship between teacher -student it’s a rescue a point, because this showed a lot of respect and cordiality between the two actors. Therefore the practice of teaching introduction to literacy is not taken with due consideration to generate a true learning.